Sosial Ekonomi Buruh Batu Putih Desa Lubuk Sepuh Kecamatan Pelawan, Kabupaten Sarolangun Tahun 1999-2020 - Nurneilina Wulandari; Azmi Fitrisia (Jurnal Kronologi, 2022)
This research is a historical study that discusses the Socio-Economic of the white stone workers in Lubuk Sepuh Village, Pelawan District, Sarolangun Regency in 1999-2020. In accordance with the main problems above, the research problems are formulated as follows: 1). How was the socio-economic change of the stone workers in Lubuk Sepuh Village before 1999. 2). How to manage white stone so that it can generate income for mining workers. The purpose of this study was to find out how the socio-economic changes of the workers in Lubuk Sepuh Village and to determine the impact of the socio-economic changes of the Batu Putih workers in Lubuk Sepuh Village. The method in this study uses a qualitative method using the following steps: 1. Heuristics, collecting various data from primary sources through interviews with actors and secondary sources from books that are relevant and related to this paper (literature study), 2) source criticism, 3) analysis, synthesis and interpretation, 4) historiography, namely writing historical data so that it becomes a writing. From the discussion, it can be seen that; First: Lubuk Sepuh Village It is one of the villages located in Pelawan District, Sarolangun Regency, because the area is rich in mining potential, namely white stone, it is used as a source of livelihood to meet the needs of life. Second, work as a stone laborer is very useful for the people of Lubuk sepuh village to fulfill their daily needs, especially for residents who have dropped out of school and residents who have families but do not have jobs, so being a white stone laborer is very helpful for residents to fulfill their needs, both in terms of economy, education and even property ownershipKeywords: Change, Socio-Economic,White Stone Worker